Doubly‐selective channel estimation with unknown interference in OFDM systems. Issue 7 (1st April 2016) - Zhou, Jingrong; Zhao, Sai; Tan, Yizhi; Qin, Jiayin
Abstract : In orthogonal frequency division multiplexing‐based spectrum sharing networks, due to inefficient coordination or imperfect spectrum sensing, the signals from femtocells or secondary users appear as interference in a subset of subcarriers of the primary systems. For pilot‐based doubly‐selective channel estimation, the embedded pilots in pilot subcarriers would inevitably be harmed by the unpredictable interference. This unsolved issue is considered and proposed is a variational expectation maximisation‐based method to iteratively learn the distribution of thermal noise plus interference, and refine doubly‐selective channel estimates. Simulations demonstrated the superiority of the proposed approach over existing algorithms without considering interference mitigation.